Academic Curriculum of the 2023 International Summer School of the “Post-Holocaust Remedies” Project - Ohm, Sabrina; Rosenfeld, Julia; Justus Liebig University Giessen (My University, 2024)
This academic curriculum aims to provide a comprehensive overview of the curriculum developed for the international Summer School of the “Post-Holocaust Remedies” Project, which took place in 2023 and offers recommendations for implementing similar teaching concepts.
Keywords: ddc:340